Polysomes of Trypanosoma brucei: association with initiation factors and RNA-binding proteins - Klein, Cornelia Andrea; Terrao, Monica; Inchaustegui Gil, Diana Patricia; Clayton, Christine (PLOS ONE, 2015)
We report here the results of experiments designed to identify RNA-binding proteins that might be associated with Trypanosoma brucei polysomes. After some preliminary mass spectrometry of polysomal fractions, we investigated the distributions of selected tagged proteins using sucrose gradients and immunofluorescence.
Gesehen am 07.07.2020